Equivalent Description of Hom-Lie Algebroids. (19th September 2018) - Xiong, Zhen
Abstract : We study representations of Hom-Lie algebroids, give some properties of Hom-Lie algebroids, and discuss equivalent statements of Hom-Lie algebroids. Then, we prove that two known definitions of Hom-Lie algebroids can be transformed into each other under some conditions.